Extensive Listening Activities of EFL Learners in Higher Level of Education - Wahidah, Farah Sukmawati; Luthfiyyah, Roghibatul (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2018)
Even the most difficult, listen to foreign language materials can be a pleasure, especially when it is done outside the classroom. Students can freely choose what they want to listen and can anywhere do listening activities. This study examines how the learners did their extensive listening activities. From all the links given, thirty-nine students who took listening course in the fourth semester only accessed youtube and chose song and movie as the materials for supporting their listening activities, and they are mostly interested in listening to song. They mostly listen to song five times a week with the duration four minutes for each listening activity.